2005
DOI: 10.1037/1528-3542.5.4.446
|View full text |Cite
|
Sign up to set email alerts
|

Mood-Congruent Attentional Bias in Dysphoria: Maintained Attention to and Impaired Disengagement From Negative Information.

Abstract: Attentional bias to negative information has been proposed to be a cognitive vulnerability factor for the development of depression. In 2 experiments, the authors examined mood-congruent attentional bias in dysphoria. In both experiments, dysphoric and nondysphoric participants performed an attentional task with negative, positive, and neutral word cues preceding a target. Targets appeared either at the same or at the opposite location of the cue. Overall, results indicate that dysphoric participants show main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
264
2
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 321 publications
(313 citation statements)
references
References 42 publications
35
264
2
4
Order By: Relevance
“…This disturbance in the attentional processing of negative information in depressive patients is not a unique finding and has already been reported within a number of recent studies reliably demonstrating maintained attention towards depression-related information and difficulties in disengaging attention away from emotional information with a negative content (e.g. Koster et al, 2005;Leyman et al, 2007).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This disturbance in the attentional processing of negative information in depressive patients is not a unique finding and has already been reported within a number of recent studies reliably demonstrating maintained attention towards depression-related information and difficulties in disengaging attention away from emotional information with a negative content (e.g. Koster et al, 2005;Leyman et al, 2007).…”
Section: Discussionsupporting
confidence: 66%
“…This is puzzling given the clinical and theoretical relevance of the question. Cognitive theories of depression have repeatedly emphasized the role of a biased processing of emotional information in the development and maintenance of depression (Beck et al, 1979;Clark et al, 1999;Beevers, 2005), with recent empirical studies reliably demonstrating a general cognitive inflexibility or inability to inhibit or to disengage from intrusive, irrelevant and negative information, leading to recurrent and remaining patterns of negative thoughts and feelings (Koster et al, 2005;Mogg and Bradley, 2005;Goeleven et al, 2006;Joormann, 2006;Leyman et al, 2007). In line with these findings, recent functional imaging studies have shown disruptions in the prefrontal activation patterns of depressive patients (Mayberg, 1997(Mayberg, , 2007Drevets, 2000;Lepp盲nen, 2006), brain regions found to be important in the implementation of top-down attentional control (MacDonald et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, many of those information-processing studies have primarily focused on memory and attention. Recent findings indicate that depressed individuals display an attentional bias for negative material at more elaborative stages of information processing (Koster et al, 2005;De Raedt and Koster, 2010). Moreover, it was found that depressed individuals had a better memory for negative information (Matt et al, 1992;Walter et al, 2007;Taylor and John, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The two-year follow-up assessment consists of a face-to-face clinic visit, in which baseline assessments -except those concerning stable concepts -are repeated. A few additional assessments were included: the CIDI bipolar disorder section, questions about experienced side effects and effectiveness of used psychotropic medication, a computerized working memory task (N-back; Carlson et al, 1998), a computerized exogeneous cueing task (Koster et al, 2005) to assess attentional bias for depression and anxiety, and an index of seasonality of symptoms (Seasonal Pattern Assessment Questionnaire; Mersch et al 2004). The four-year and eight-year follow-up assessments will start in September 2008 and 2012, respectively.…”
Section: Time Line and Follow-up Assessmentsmentioning
confidence: 99%